The Impact of Online-Schooling during COVID-19 on Device-Measured 24-Hour Movement Behaviours among High School Students: A Compositional Data Analysis - Petra Starbek; Kaja Kastelic; Nejc Šarabon (MDPI AG, 2022)
The COVID-19 measures have unfavourably affected the movement behaviours of youth. The aim of this study was to explore the impact of online-schooling during COVID-19 on device-measured sleep (SL), sedentary behaviour (SB), light physical activity (LPA), and moderate-vigorous physical activity (MVPA) among high school students. A total of 51 students (26 female) from Slovenia wore an activity monitor activPAL4 during the weekdays of onsite-schooling and during the weekdays of online-schooling. Data on movement behaviours were analysed using compositional data analysis. During the onsite-schooling (and online-schooling), students spent on average 432 min/day (469 min/day) in SL, 731 (755) in SB, 253 (202) in LPA, and 25 (15) in MVPA. Repeated measures multivariate analysis of variance confirmed significantly more time was spent in SL (log ratio 0.29; 95% CI 0.20, 0.37)) and SB (log ratio 0.23; 95% CI 0.13, 0.32) and less time in MVPA (log ratio −0.44; 95% CI −0.66, −0.23) during the online-schooling weekdays. Students spent significantly more time in SB during leisure (log ratio 0.20; 95% CI 0.06, 0.35) as well as during lecture time (log ratio 0.45; 95% CI 0.32, 0.58). Our results indicate that online-schooling significantly contributed to the unfavourable changes in students' movement behaviours during COVID-19. Future studies should focus on developing physical activity interventions suitable for the circumstances of the epidemic.